NILAI-NILAI INTI (CORE VALUE) MASYARAKAT ISLAM DI MERUHUM PULAU LEMUKUTAN - Imron Muttaqin (Khatulistiwa, 2014)
This articles based on program called by “Kampung Riset” held by Lembaga Penelitian dan Pengabdian pada Masyarakat (LP2M) IAIN Pontianak. The aims of this study is to describe the core value of Islamic Meruhum society. Interview and participant observation collecting data used. Informan key choosen by purposive sampling technique. The finding of this study shows the core values in Meruhum, they are cooperation, hard work and kinship. The Meruhum’s Islamic culture is circumcision, weddings, Muharram celebration, tahlil (repeated recitation of the confession of faith). Education and internalization of Islamic culture values are more to be aplicated through direct practice in a particular job than formal education. Kalimah thayyibah are loaded and inserted when life skills education practice are held. Along with it, internalization of Islamic aqeedah and teaching process are included.